IMPLEMENTASI PROGRAM INTEGRASI LAYANAN PRIMER (ILP) DALAM UPAYA PENINGKATAN KESEHATAN MASYARAKAT DI INDONESIA – SYSTEMATIC REVIEW - Jannah, Putri Isriyatil; Eliana, Desy; Anindya, Fauzia Liesly; Trisasri, Ruri; Awaludin; Rizki, Rahmat Kurniawan (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2026)
Background: Primary health care plays a key role in ensuring the achievement of Universal Health Coverage (UHC), which is a main goal in the global health system. As one effort to strengthen primary health care services, the Indonesian government launched the Integrated Primary Care (IPC) Program (Program Integrasi Layanan Primer - ILP). Objective: This study aims to determine and analyze the implementation of the ILP program as an effort to improve public health in Indonesia. Methods: Literature searches were conducted using the Google Scholar databases, using the keywords: